An overview and trend analysis of research on the relationship between urban streets and residents' health in China pre- and post COVID-19 pandemic - Meng, Lingchao; Wen, Kuo-Hsun (Frontiers in Public Health, 2023)
Introduction After the outbreak of COVID-19, the international community has been faced with various problems it has brought to cities. A large number of research projects and corresponding management measures were launched globally, trying to reduce the impact of COVID-19 on society. Among them, exploring how to maintain the health of residents by managing and updating the design of urban streets is one of the important issues regarding urban sustainability in the post-epidemic era. Methods This study uses bibliometric analysis techniques to obtain an overview of the knowledge structure of 898 Chinese urban streets and residents' health relationship studies from the China National Knowledge Infrastructure (CNKI) database for two periods (1999–2019 and 2020–2022). Five aspects were analyzed in terms of the keyword domain co-occurrence network, topic evolution path, emergent terms, hierarchical clustering, and confusion matrix. Results and discussion The findings revealed that studies focused on six broad themes: community residents, health surveys, health education, COVID-19, healthy city, and public health. Based on these findings, the paper compares and discusses research priorities before and after the outbreak and highlights areas for further research and attention.